2014
DOI: 10.1128/mcb.01701-13
|View full text |Cite
|
Sign up to set email alerts
|

The Catalytic Activity of the Mitogen-Activated Protein Kinase Extracellular Signal-Regulated Kinase 3 Is Required To Sustain CD4+ CD8+ Thymocyte Survival

Abstract: Extracellular signal-regulated kinase 3 (ERK3) is an atypical member of the mitogen-activated protein kinase (MAPK) family whose function is largely unknown. Given the central role of MAPKs in T cell development, we hypothesized that ERK3 may regulate thymocyte development. Here we have shown that ERK3 deficiency leads to a 50% reduction in CD4 ؉ CD8 ؉ (DP) thymocyte number. Analysis of hematopoietic chimeras revealed that the reduction in DP thymocytes is intrinsic to hematopoietic cells. We found that early … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 49 publications
(73 reference statements)
2
30
0
Order By: Relevance
“…Previous work from our laboratory has also shown that the thymic epithelium contributes to the decreased generation of SP thymocytes in the absence of ERK3 . However, we do not think that ERK3 deficency in the epithelium is responsible for the defective positive selection phenotype because we could recapitulate the results with in vitro stimulation of thymocytes.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Previous work from our laboratory has also shown that the thymic epithelium contributes to the decreased generation of SP thymocytes in the absence of ERK3 . However, we do not think that ERK3 deficency in the epithelium is responsible for the defective positive selection phenotype because we could recapitulate the results with in vitro stimulation of thymocytes.…”
Section: Discussionmentioning
confidence: 75%
“…To bypass this problem, we have introduced already rearranged TCR‐ α and TCR‐ β transgenes into the ERK3‐deficient background. As previously shown, introduction of the OT‐II TCR specific for ovalbumin in the context of the MHC class II molecule I‐A b restores thymic cellularity and DP thymocyte number allowing us to study further steps in T‐cell differentiation (Fig. ).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In case of apoptosis induction in antigen receptor-stimulated B and T cells, inhibition of p38 MAPK activity by SB203580 did not affect apoptosis induction in both cell types (Salmon et al 1997). in the half-life of double-positive thymocytes, associated with a higher level of apoptosis, as well as impaired positive selection (Marquis et al 2014b;Sirois et al 2014). Thus, p38 MAPK signaling can exert agonistic or antagonistic effects on apoptosis induction, which is dependent on the cell type and context.…”
Section: The P38 Pathwaymentioning
confidence: 99%